DUKUNGAN SOSIAL DAN MOTIVASI BERHUBUNGAN DENGAN KEPATUHAN PEMBATASAN ASUPAN CAIRAN PADA PASIEN PENYAKIT GINJAL KRONIK YANG MENJALANI HEMODIALISIS - Hartin I.K Nadi; Ninuk Dian Kurniawati; Herdina Mariyanti (Universitas Airlangga, 2019)
Introduction: Adherence on fluid intake restriction is one of the problems of chronic kidney disease patients on hemodialysis. Poor adherence could lead to treatment failure this inturn lower quality of life for patients, increase morbidity and mortality. Social support and motivation are important factors of adherence on fluid intake restriction among patients with chronic kidney disease undergone hemodialysis. The aimed of this study was two fold. Firstly, it aimed to identify the relationship between social support and motivation with adherence on fluid intake restriction among patients with chronic kidney disease undergone hemodialysis. Secondly it analyzed relationship between both variable.Methods: This study used cross-sectional design. Samples were patients with chronic kidney disease undergone hemodialysis at RSUD Dr. M.M. Dunda Limboto, Kabupaten Gorontalo. The independent variables were social support and motivation. The dependent variable was adherence on fluid intake restriction. Sample were 19 individuals, recruited using consecutive sampling. Data were collected through questionnaire and analyzed by of Spearmen Rho statistical test with significance level of α<0.05.Result: Result of the research showed that there was a relationship between social support and motivation with adherence on fluid intake restriction among patients with chronic kidney disease undergone hemodialysis with significance level p=0.000 it means the relationship between two variable was reliable. The higher the social support, the better patients adherence on fluid restriction. The limitation of this research was small sample size to be used.Conclusion: It can be conclude that there was relationship between social support and motivation with adherence on fluid intake restriction among patients with chronic kidney disease undergone hemodialysis. Further studies should involve more respondents.